2016
DOI: 10.1002/cctc.201501341
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Morphology and Efficiency of Nanostructured Molybdenum Nitride Electrocatalysts for the Hydrogen Evolution Reaction

Abstract: Among catalysts based on non‐noble metals, Mo‐based materials are important for hydrogen evolution because of their low cost, good conductivity, and catalytic efficiency. This study demonstrates a facile two‐step synthesis of Mo2N nanostructures assembled from 5–8 nm particles with graphitic carbon nitride as the nitrogen source. These Mo2N nanostructures of various morphologies (hexagons, triangles, and nanowires) show a very high activity and stability in acidic media during water electrolysis. Their nanostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 39 publications
1
46
0
1
Order By: Relevance
“…[28] Furthermore, the Ni 2p spectrumc ontained two prominent shake-up satellites peaks at 861.7 and 879.3 eV,w hereas the peak at 852.5 eV was assigned to metallic nickel. [23,[25][26][27][28][29] The TEM images and corresponding EDS mapping analysiso fasingle nanowire further revealed the homogeneous distribution of Ni, Mo, O, or Ni nt he precursor NiMoO 4 nanowires and the as-synthesized NiMoN nanowires (Figure 2g,h). The Mo 2/3 + in the metal nitride is thought to be activef or HER whereas the presence of Mo 3/4 + and Mo 6 + speciesw as due to the surface oxidization of Mo 2/3 + upon air exposure.…”
Section: Resultsmentioning
confidence: 89%
“…[28] Furthermore, the Ni 2p spectrumc ontained two prominent shake-up satellites peaks at 861.7 and 879.3 eV,w hereas the peak at 852.5 eV was assigned to metallic nickel. [23,[25][26][27][28][29] The TEM images and corresponding EDS mapping analysiso fasingle nanowire further revealed the homogeneous distribution of Ni, Mo, O, or Ni nt he precursor NiMoO 4 nanowires and the as-synthesized NiMoN nanowires (Figure 2g,h). The Mo 2/3 + in the metal nitride is thought to be activef or HER whereas the presence of Mo 3/4 + and Mo 6 + speciesw as due to the surface oxidization of Mo 2/3 + upon air exposure.…”
Section: Resultsmentioning
confidence: 89%
“…Additionally, recent studies have confirmed molybdenum‐based catalysts such as molybdenum boride, molybdenum nitride, molybdenum disulfide, molybdenum phosphide, and molybdenum carbide own excellent HER catalytic activity. Considering the part structure drawbacks of metal@heteroatoms‐doped carbon, it is inspiring for us to deal with this problem by introducing additional active nanoparticles on metal@heteroatoms‐doped carbon structure aiming at providing abundant active sites for HER.…”
Section: Introductionmentioning
confidence: 95%
“…Herein, we successfully endowC o 4 Nw ith prominent HER catalytic capability by tailoring the positions of the d-band center through transitionmetal doping.T he V-doped Co 4 Nn anosheets displaya n overpotential of 37 mV at 10 mA cm À2 ,w hich is substantially better than Co 4 Na nd even close to the benchmark Pt/C catalysts.X ANES,U PS,a nd DFT calculations consistently reveal the enhanced performance is attributed to the downshift of the d-band center,w hich helps facilitate the Hd esorption. [8] Va rious transition-metal nitrides,s uch as MoN, [9] Ni 3 N, [10] WN, [11] and alloyed metal nitrides, [3a, 12] have been reported to be HER catalysts in alkaline media. [1] Alkaline electrolysis has been viewed as the most feasible way for the industrial production of hydrogen.…”
mentioning
confidence: 99%
“…[8] Va rious transition-metal nitrides,s uch as MoN, [9] Ni 3 N, [10] WN, [11] and alloyed metal nitrides, [3a, 12] have been reported to be HER catalysts in alkaline media. [8] Va rious transition-metal nitrides,s uch as MoN, [9] Ni 3 N, [10] WN, [11] and alloyed metal nitrides, [3a, 12] have been reported to be HER catalysts in alkaline media.…”
mentioning
confidence: 99%